Derivados de tanino de tara (caesalpinia spinosa) en formulaciones antiincrustantes - Bellotti, Natalia (2012)
AF coatings prevent the undesirable accumulation of a wide variety of marine organisms (biofouling) on ship hulls can lead to significant increased costs, principally by increased fuel consumption. The bioactive compounds (biocides) used in antifouling coatings, like tributyltin (TBT), are banned for their toxic action towards non-target marine organisms. As a consequence, the development of alternative AF coatings with new natural products as biocides inhibit is a key factor. In this approach, tara (Caesalpinia spinosa) tannin (TT) derivatives are being proposed as a promising solution. The aim of this research work was, primarily, to explore the possible application of a natural and abundant product, such as the TT, in the preparation of AF coatings. So, two TT derivatives were obtained at different temperatures (20ºC and 60ºC) as immersion in natural environments, the dissolution of TT from coatings in artificial sea water was studied. Antifouling paints with a soluble matrix were formulated and their action was assessed in natural sea water environment (Mar del Plata harbor).